PENGARUH PEMROSESAN INFORMASI SECARA SENTRAL DAN PERIFERAL “PESAN SOCIAL MEDIA” TERHADAP KEPUTUSAN MEMILIH JASA JNE DI JAKARTA BARAT - Ramadhani, Nadhilah; Tri Atmodjo, Juwono (Jurnal Visi Komunikasi, 2020)
The development of technology today, Social Media has become a tool used by companies to help prospective customers process information that suits their needs. Companies that utilize social media as marketing tools are PT. Tiki Line Nugraha Ekakurir, better known as JNE. JNE uses Instagram to provide information. This study is to determine the extent of the influence of Central Information Processing "Social Media Message" Against the Decision to Choose JNE Services in West Jakarta with the Elaboration Likelihood Model theory. This study uses a quantitative approach to the type of explanatory research. With the survey method by distributing questionnaires to 196 respondents obtained from calculations using the purposive sampling technique. The data analysis technique used is a Likert scale with data analysis of multiple linear regression equations. The results of this study are customers who have research criteria only 161 respondents. There is an influence between Central Information Processing of 39.2% and Peripherals of 65.5%. And there is a joint influence on the Decision to Choose JNE Services by 68.4%. Based on the research results, the researcher gave a suggestion that the JNE social media team could focus the content delivered in the form of information packaged more simply and easily understood, although central information such as information related to tariffs, types of services including promo or discount programs still needed to be informed.